A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting and its preparation method

By using high-calcium magnesium calcium zirconium sand and magnesium perovskite sand and combined with composite bonding agent to prepare high-calcium magnesium perovskite zirconium bricks, the existing magnesium calcium bricks have been solved, and the efficient and long-lived refractory materials have been achieved, which significantly improves the performance and efficiency of stainless steel smelting.

CN119241215BActive Publication Date: 2025-03-14LIAONING ZHONGMEI HIGH TEMPERATURE MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411773861.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing magnesium-calcium bricks for stainless steel smelting have a short service life and poor purification effect on the molten steel, which limits the development of the stainless steel and special steel smelting industry.

Method used

High-calcium magnesium calcium zirconium sand and magnesium perovskite sand are used as the main raw materials, and high-calcium magnesium perovskite bricks are prepared with composite bonding agents. Through high-pressure molding and high-temperature firing processes, the volume density, high-temperature resistance and corrosion resistance of the bricks are improved.

Benefits of technology

It achieves high volume density, low porosity, low impurity, high temperature resistance, corrosion resistance, slag resistance and high temperature wear resistance, extends service life and significantly improves the purification effect of molten steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of refractory materials, and relates to a high calcium magnesium calcium titanium zirconium brick for stainless steel smelting and a preparation method thereof. The present invention aims to replace the existing magnesium calcium brick for stainless steel smelting by preparing high calcium magnesium calcium zirconium sand, magnesium calcium titanium sand, and composite binder for oil shaft kiln. The high calcium magnesium calcium titanium zirconium brick has the characteristics of high bulk density, low pores and low impurities, and better high temperature resistance, corrosion resistance, slag resistance and high temperature wear resistance, and finally meets the purpose of replacing the traditional magnesium calcium brick refractory material for stainless steel smelting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and specifically relates to a high-calcium-magnesium calcium-titanium-zirconium brick for stainless steel smelting and a preparation method thereof. Background Art

[0002] Magnesia-calcium bricks are widely used in stainless steel and special steel smelting furnaces because free CaO in them can purify molten steel. At present, magnesia-calcium bricks used in stainless steel and special steel smelting furnaces generally use sintered magnesia-calcium sand as raw material to produce magnesia-calcium bricks with a CaO content of 20%~30%. The porosity of such magnesia-calcium bricks is generally 8%~12%, and the volume density is 3.00g / cm 3 The sum of the three impurities SiO2, Al2O3 and Fe2O3 is about 2%~3%, the CaO content is low, and the effect of purifying molten steel is not obvious.

[0003] With the gradual increase in the production capacity of stainless steel and clean steel in my country, the related supporting smelting has gradually achieved large-scale development and the smelting process has developed rapidly. The service life of the supporting refractory materials and the low steel liquid purification effect have become objective factors affecting the development of smelting technologies such as AOD furnaces and GOR furnaces.

[0004] In view of the above situation, a high-calcium and long-life product has been developed to replace the existing magnesium-calcium refractory materials used in stainless steel smelting, which has important practical significance and application prospects for the sustainable development of stainless steel smelting. Summary of the invention

[0005] In order to solve the above problems, the purpose of the present invention is to provide a high calcium magnesium calcium titanium zirconium brick for stainless steel smelting and a preparation method thereof. It is intended to replace the existing magnesium calcium brick for stainless steel smelting. The high calcium magnesium calcium titanium zirconium brick has the characteristics of high volume density, low porosity, low impurities, high temperature resistance, corrosion resistance, slag resistance and high temperature wear resistance, and finally meets the purpose of replacing the traditional magnesium calcium brick refractory material for stainless steel smelting.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions.

[0007] A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting, comprising the following raw materials in parts by weight:

[0008] 5 to 13 parts of 8mm~5mm high calcium magnesium calcium zircon sand for oil vertical kiln, 30 to 45 parts of 5mm~2mm high calcium magnesium calcium zircon sand for oil vertical kiln, 12 to 25 parts of 2mm~0mm high calcium magnesium calcium zircon sand for oil vertical kiln, 0 to 5 parts of 5mm~2mm magnesium calcium titanium sand, 0 to 5 parts of 2mm~0mm magnesium calcium titanium sand, 5 to 10 parts of fine powder of high calcium magnesium calcium zircon sand for oil vertical kiln ≤ 0.074mm, 5 to 10 parts of ultrafine powder of magnesium calcium titanium sand ≤ 0.037mm, and 3 to 5 parts of composite binder.

[0009] Furthermore, the composite binder includes the following raw materials in parts by weight: 30-40 parts of zirconium tetrachloride, 5-10 parts of ammonia, 5-10 parts of propanol, and 40-60 parts of industrial dextrin; the above raw materials are mixed, cooled, separated, hydrolyzed and precipitated, filtered, dissolved and crystallized, and then prepared in a vacuum reactor.

[0010] Furthermore, the physical and chemical indicators of high calcium magnesium calcium zirconium sand and magnesium calcium titanium sand of the oil shaft kiln are shown in Table 1.

[0011] Table 1 Physical and chemical indicators of magnesium calcium titanium sand and oil shaft kiln high calcium magnesium calcium zirconium sand

[0012]

[0013] Note: % is mass percentage.

[0014] Furthermore, magnesium calcium titanium sand: 93% of waste high-calcium dolomite and 7% of titanium concentrate are used as raw materials. After crushing, grinding and high-pressure ball pressing, they are put into an electric arc furnace for high-temperature calcination above 2000°C. The finished product after calcination is kept warm for 8 hours, naturally cooled, and magnesium calcium titanium sand is selected.

[0015] The magnesium calcium titanium sand synthesized in the present invention has the advantages of high bulk density and low impurities compared with traditional magnesium calcium sand. The detailed indicators of traditional magnesium calcium sand are shown in Table 2.

[0016] Table 2 Physical and chemical indexes of magnesium calcium sand

[0017]

[0018] Note: % is mass percentage.

[0019] Furthermore, the oil-fired vertical kiln high calcium magnesium calcium zirconium sand is obtained by grinding 66% high-grade calcium hydroxide, 2% desiliconized zirconium and 32% light-burned magnesium powder in a mass ratio, pressing into balls, and sending them into a high-temperature oil-fired vertical kiln for calcination. It is calcined at above 1680°C, naturally cooled, and crushed for selection.

[0020] Compared with traditional magnesium calcium sand, oil vertical kiln high calcium magnesium calcium zirconium sand has the advantages of high calcium, high bulk density and low impurities. The detailed indicators of traditional magnesium calcium sand are shown in Table 2.

[0021] A method for preparing high calcium magnesium perovskite zirconium bricks for stainless steel smelting comprises the following steps:

[0022] Step 1, raw material crushing: crush, screen and grind the high calcium magnesium calcium zirconium sand and magnesium calcium titanium sand of the oil shaft kiln into particles and fine powder of different particle sizes;

[0023] Step 2, premixing fine powder: the oil shaft kiln high calcium magnesium calcium zirconium sand fine powder and magnesium calcium titanium sand ultrafine powder crushed in step 1 are mixed evenly according to the required mass fraction to obtain premixed fine powder;

[0024] Step 3, mixing: the different granular raw materials in step 1 are fed into a high-speed mixer in the order of feeding for mixing for 5 minutes, and then the composite binder is added and mixed for 5 minutes, and then the fine powder premixed in step 2 is added and mixed for 8 minutes, and the material is discharged after mixing evenly to obtain a mud material;

[0025] Step 4, molding: weigh the clay material of step 3 of a specified weight, evenly place it into the mold cavity of the brick press, and mold it under high pressure to obtain a molded brick;

[0026] Step 5, stacking bricks: stacking the above-mentioned formed bricks on the tunnel kiln car;

[0027] Step 6, firing: the kiln car with the formed bricks is fired at high temperature in a tunnel kiln;

[0028] Step 7: Picking, processing and packaging: After the formed bricks are cooled out of the kiln, they are picked, packaged and then put into the finished product warehouse.

[0029] Furthermore, step 1 is specifically to crush, screen and grind the oil shaft kiln high calcium magnesium calcium zircon sand and magnesium calcium titanium sand through a jaw crusher, a roll crusher and a Raymond mill to make oil shaft kiln high calcium magnesium calcium zircon sand granules with particle sizes of 8mm~5mm, 5mm~2mm, and 2mm~0mm, respectively, 5mm~2mm, 2mm~0mm magnesium calcium titanium sand granules, ≤0.074mm oil shaft kiln high calcium magnesium calcium zircon sand fine powder, ≤0.037mm magnesium calcium titanium sand ultrafine powder.

[0030] Furthermore, in step 3, the order of adding materials is: first 8mm~5mm oil shaft kiln high calcium magnesium calcium zircon sand, then 5mm~2mm and 2mm~0mm oil shaft kiln high calcium magnesium calcium zircon sand, 5mm~2mm and 2mm~0mm magnesium calcium titanium sand, then add the composite binder to mix, and finally add the premixed fine powder of step 2.

[0031] Furthermore, in step 6, the high temperature sintering temperature is 1650°C to 1700°C.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows.

[0033] The invention adopts independently developed oil shaft kiln high calcium magnesium calcium zirconium sand and magnesium calcium titanium sand as main raw materials for preparation.

[0034] 1. The high calcium magnesium calcium zirconium sand introduced from the oil shaft kiln has low porosity, high volume density and dense bonding; the activity of MgO and CaO is significantly reduced, and it has good resistance to hydration; the content of three impurities SiO2, Al2O3 and Fe2O3 is low, and there are few low-melting-point substances; the introduced Zr2O3 can generate high-melting-point mineral CaZrO3 and form a stable Zr2O3 solid solution, which can effectively improve the thermal shock stability of the material, improve toughness and anti-flaking properties. In addition, its wetting angle is increased and the metal stability is better, that is, it is not easily wetted by liquid metal, which improves the anti-penetration and anti-corrosion properties.

[0035] 2. The introduced magnesium calcium titanium sand uses waste high calcium magnesite, which is much cheaper than magnesite. It is expected that the cost of brick making will be reduced by more than 5%, and the life of the manufactured products will be more than 10% higher than the existing magnesium calcium bricks. While increasing the economic added value of the products, it can also open up a road that is more suitable for corporate benefits driven by scientific and technological research and development, realize the intensive utilization of waste magnesite, and achieve the development goal of green environmental protection. It solves the problem of premature offline due to the rapid local erosion and loss of current products. It is expected that the average furnace life will be increased by more than 10%, achieving the goal of high efficiency, long life and cleanliness of stainless steel and special steel smelting, and reducing costs for steel companies.

[0036] 3. The high melting point mineral CaZrO3 and stable Zr2O3 solid solution in the high calcium magnesium calcium zirconium sand introduced into the oil shaft kiln can improve the thermal shock stability and spalling resistance of the product. In addition, its wetting angle is increased, and it is not easily wetted by liquid metal, which improves the anti-penetration and anti-corrosion performance.

[0037] 4. The CaTiO3 in the introduced magnesium calcium titanium sand exists in the grain boundary of the main crystal phase, providing a rapid migration path for atomic diffusion and promoting sintering. In addition, the presence of CaTiO3 causes f-CaO to exist in a discontinuous manner, which improves the anti-hydration performance of the product.

[0038] 5. Strengthen the matrix with high calcium magnesium calcium zirconium sand from oil shaft kiln with particle size less than 0.074mm and ultrafine magnesium calcium titanium sand with particle size less than 0.037mm to increase its specific surface area, reduce sintering temperature, and make sintering easier. After high temperature sintering, the matrix part of the product is more densely bonded, which improves the bulk density and compressive strength, increases the direct bonding strength between particles, and improves high temperature strength and thermal shock stability.

[0039] 6. The existing binder of magnesium-calcium bricks is generally semi-refined paraffin wax at 56°C~60°C. Due to the high melting point of the paraffin wax, the temperature requirement of the mud material is very strict. The mud material temperature must be heated to above 60°C so that the paraffin wax can be well dispersed, evenly wrapped on the surface of the particles and wet the fine powder. However, the mud material above 60°C will produce cracks during molding because the gas cannot be removed in time. In order to avoid molding cracks, a cooling process must be added to reduce the mud material temperature to below 45°C for molding. The above is a traditional production process. The friction brick press is used for molding, which can obtain a higher volume density and a lower porosity, but the process is cumbersome and complicated, and it will greatly increase manpower and production costs. It is very impractical for the molding process of the fully automatic brick press. The role of paraffin wax as a binder is to improve the strength and refractoriness of the brick blank. The composite binder mentioned in the patent of the present invention is prepared from zirconium tetrachloride, ammonia, propanol, industrial dextrin and water after cooling, separation, hydrolysis precipitation, filtration, drying, dissolution-crystallization reaction; the composite binder can improve the density and thus improve the high temperature resistance, corrosion resistance and slag resistance of the brick, while reducing the molding and drying process, greatly optimizing the production process.

[0040] To sum up, the high calcium magnesium calcium titanium zirconium brick for stainless steel smelting produced by the present invention is a product with a calcium content of more than 55%, which has a very large purification effect on molten steel. It has high bulk density, low porosity, low impurities, high temperature resistance, corrosion resistance, slag resistance and high temperature wear resistance. It is a better substitute for existing magnesium calcium bricks, and better serves the smelting of stainless steel and special steel. At the same time, it completely solves the problems of refractory quality and purification of molten steel that restrict the development of the stainless steel and special steel smelting industry, and finally meets the purpose of replacing traditional magnesium calcium refractory materials. DETAILED DESCRIPTION

[0041] In order to make those skilled in the art better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. These embodiments should be understood to be only used to illustrate the present invention and not to limit the protection scope of the present invention. After reading the contents recorded in the present invention, all other embodiments obtained after various changes or modifications made to the present invention based on the technical solution and embodiments of the present invention also fall within the scope of protection of the claims of the present invention.

[0042] A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting, comprising the following raw materials in parts by weight:

[0043] 5 to 13 parts of 8mm~5mm high calcium magnesium calcium zircon sand for oil vertical kiln, 30 to 45 parts of 5mm~2mm high calcium magnesium calcium zircon sand for oil vertical kiln, 12 to 25 parts of 2mm~0mm high calcium magnesium calcium zircon sand for oil vertical kiln, 0 to 5 parts of 5mm~2mm magnesium calcium titanium sand, 0 to 5 parts of 2mm~0mm magnesium calcium titanium sand, 5 to 10 parts of fine powder of high calcium magnesium calcium zircon sand for oil vertical kiln ≤0.074mm, 5 to 10 parts of ultrafine powder of magnesium calcium titanium sand ≤0.037mm, and 3 to 5 parts of composite binder.

[0044] Furthermore, the composite binder comprises the following raw materials in parts by weight: 35 parts of zirconium tetrachloride, 5 parts of ammonia, 5 parts of propanol, and 55 parts of industrial dextrin.

[0045] First, 35 parts of zirconium tetrachloride, 5 parts of ammonia and 5 parts of propanol are stirred evenly in a vacuum reactor, and then hydrolyzed, precipitated, filtered, dissolved and crystallized. 55 parts of industrial dextrin are added and mixed in a closed container. The mixed solution is cooled and separated in a cooling tower to prepare the product. The composite binder can make a large number of secondary zirconium spinels appear between the magnesia sand particles in the brick, improve the density and thus improve the high temperature resistance, corrosion resistance and slag resistance of the brick.

[0046] Furthermore, the physical and chemical indicators of high calcium magnesium calcium zirconium sand and magnesium calcium titanium sand of oil shaft kiln are shown in Table 1.

[0047] Furthermore, magnesium calcium titanium sand is made of 93% waste high-calcium dolomite and 7% titanium concentrate in a mass ratio as raw materials, which are crushed, ground and high-pressure pelletized, and then put into an electric arc furnace for high-temperature calcination above 2000°C. The finished product after calcination is kept warm for 8 hours, naturally cooled, and magnesium calcium titanium sand is selected.

[0048] The magnesium calcium titanium sand synthesized in the present invention has the advantages of high bulk density and low impurities compared with traditional magnesium calcium sand. The detailed indicators of traditional magnesium calcium sand are shown in Table 2.

[0049] Furthermore, the oil-fired vertical kiln high calcium magnesium calcium zirconium sand is obtained by grinding 66% high-grade calcium hydroxide, 2% desiliconized zirconium and 32% light-burned magnesium powder in a mass ratio, pressing into balls, and sending them into a high-temperature oil-fired vertical kiln for calcination. It is calcined at above 1680°C, naturally cooled, and crushed for selection.

[0050] Compared with traditional magnesium calcium sand, oil vertical kiln high calcium magnesium calcium zirconium sand has the advantages of high calcium, high bulk density and low impurities.

[0051] Furthermore, the binder is a composite binder, which can make a large amount of secondary zirconium spinel tend to appear between the magnesia sand particles in the brick, thereby improving the density and thus improving the high temperature resistance, corrosion resistance and slag resistance of the brick.

[0052] A method for preparing high calcium magnesium perovskite zirconium bricks for stainless steel smelting comprises the following steps:

[0053] Step 1, raw material crushing: the oil shaft kiln high calcium magnesium calcium zircon sand and magnesium calcium titanium sand are crushed, screened and ground by a jaw crusher, a roll crusher and a Raymond mill to produce oil shaft kiln high calcium magnesium calcium zircon sand granular materials with particle sizes of 8mm~5mm, 5mm~2mm, 2mm~0mm, 5mm~2mm, 2mm~0mm magnesium calcium titanium sand granular materials, ≤0.074mm oil shaft kiln high calcium magnesium calcium zircon sand fine powder, ≤0.037mm magnesium calcium titanium sand ultrafine powder;

[0054] Step 2, premixing fine powder: the oil shaft kiln high calcium magnesium calcium zirconium sand fine powder and magnesium calcium titanium sand ultrafine powder crushed in step 1 are mixed evenly according to the required mass fraction to obtain premixed fine powder;

[0055] Step 3, mixing: the different granular raw materials in step 1 are fed into a high-speed mixer in the order of feeding for mixing, and the mixing is carried out for 5 minutes, and then the composite binder is added and mixed for 5 minutes, and then the fine powder premixed in step 2 is added and mixed for 8 minutes, and the material is discharged after mixing evenly to obtain a mud material; the feeding order is: first 8mm~5mm oil shaft kiln high calcium magnesium calcium zircon sand, then 5mm~2mm and 2mm~0mm oil shaft kiln high calcium magnesium calcium zircon sand, 5mm~2mm and 2mm~0mm magnesium calcium titanium sand, then add the composite binder and mix, and finally add the premixed fine powder in step 2;

[0056] Step 4, molding: weigh the clay material of step 3 of a specified weight, evenly place it into the mold cavity of the brick press, and mold it under high pressure to obtain a molded brick;

[0057] Step 5, stacking bricks: stacking the above-mentioned formed bricks on the tunnel kiln car;

[0058] Step 6, firing: the kiln cart with the formed bricks is fired in a tunnel kiln at a high temperature of 1650°C to 1700°C;

[0059] Step 7: Picking, processing and packaging: After the formed bricks are cooled out of the kiln, they are picked, packaged and then put into the finished product warehouse.

[0060] Example 1.

[0061] A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting is made of the following raw materials in proportion by weight:

[0062] 10 parts of 8mm~5mm oil vertical kiln high calcium magnesium calcium zircon sand, 40 parts of 5mm~2mm oil vertical kiln high calcium magnesium calcium zircon sand, 25 parts of 2mm~0mm oil vertical kiln high calcium magnesium calcium zircon sand, 3 parts of 5mm~2mm magnesium calcium titanium sand, 2 parts of 2mm~0mm magnesium calcium titanium sand, 5 parts of oil vertical kiln high calcium magnesium calcium zircon sand fine powder ≤0.074mm, 5 parts of magnesium calcium titanium sand ultrafine powder ≤0.037mm, 5 parts of composite binder;

[0063] The physical and chemical indicators of the magnesium calcium titanium sand and the oil shaft kiln high calcium magnesium calcium zirconium sand in this embodiment are shown in Table 3.

[0064] Table 3 Physical and chemical indicators of magnesium calcium titanium sand and oil shaft kiln high calcium magnesium calcium zirconium sand

[0065]

[0066] Note: % is mass percentage.

[0067] The preparation method of the high calcium magnesium perovskite zirconium brick for stainless steel smelting comprises the following process steps:

[0068] (1) Raw material crushing: The oil shaft kiln high calcium magnesium calcium zircon sand and magnesium calcium titanium sand are crushed, screened and ground by a jaw crusher, a roll crusher and a Raymond mill to produce oil shaft kiln high calcium magnesium calcium zircon sand granular materials with particle sizes of 8mm~5mm, 5mm~2mm and 2mm~0mm, magnesium calcium titanium sand granular materials with particle sizes of 5mm~2mm and 2mm~0mm, oil shaft kiln high calcium magnesium calcium zircon sand fine powder with a particle size of ≤ 0.074mm, and magnesium calcium titanium sand ultrafine powder with a particle size of ≤ 0.037mm;

[0069] (2) Premixing fine powder: the oil shaft kiln high calcium magnesium calcium zirconium sand fine powder and the magnesium calcium titanium sand ultrafine powder after the crushing in step 1 are mixed evenly according to the required weight proportion to obtain premixed fine powder;

[0070] (3) Preparation of composite binder: First, 35 parts of zirconium tetrachloride, 5 parts of ammonia and 5 parts of propanol are stirred evenly in a vacuum reactor, and then hydrolyzed, precipitated, filtered, dissolved and crystallized. Then, 55 parts of industrial dextrin are added and mixed in a closed container. The mixed solution is cooled and separated in a cooling tower to prepare the composite binder.

[0071] (4) Mixing: All raw materials are fed into a high-speed mixer according to the required weight for mixing. The order of adding materials is first 8mm~5mm oil shaft kiln high calcium magnesium calcium zircon sand, then 5mm~2mm and 2mm~0mm oil shaft kiln high calcium magnesium calcium zircon sand, 5mm~2mm and 2mm~0mm magnesium calcium titanium sand, then add the composite binder and mix, and finally add the premixed fine powder in step 2;

[0072] (5) Molding: Weigh the specified weight of clay, evenly place it into the mold cavity of the brick press, and mold it under high pressure to obtain a molded brick;

[0073] (6) Stacking bricks: stacking the above-mentioned formed bricks on the tunnel kiln car;

[0074] (7) Firing: The kiln cart with the formed bricks is fired in a tunnel kiln at a high temperature of 1650°C to 1700°C;

[0075] (8) Sorting, processing and packaging: After the formed bricks are cooled out of the kiln, they are sorted, packaged and then put into the finished product warehouse.

[0076] The test results of the finished product of this embodiment are shown in Table 6.

[0077] Example 2.

[0078] A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting is made of the following raw materials in proportion by weight:

[0079] 10 parts of 8mm~5mm high calcium magnesium calcium zircon sand for oil vertical kiln, 38 parts of 5mm~2mm high calcium magnesium calcium zircon sand for oil vertical kiln, 22 parts of 2mm~0mm high calcium magnesium calcium zircon sand for oil vertical kiln, 5 parts of 5mm~2mm magnesium calcium titanium sand, 5 parts of 2mm~0mm magnesium calcium titanium sand, 15 parts of ≤0.074mm high calcium magnesium calcium zircon sand fine powder for oil vertical kiln, 5 parts of ≤0.037mm magnesium calcium titanium sand ultrafine powder, and 4 parts of composite binder.

[0080] The physical and chemical indicators of the high calcium magnesium calcium zirconium sand and magnesium calcium titanium sand in the oil shaft kiln of this embodiment are shown in Table 3.

[0081] The process steps of the preparation method of the high calcium magnesium perovskite brick for stainless steel smelting are the same as those of Example 1; the test results of the finished product of this example are shown in Table 6.

[0082] Example 3.

[0083] A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting is made of the following raw materials in proportion by weight:

[0084] 10 parts of 8mm~5mm oil vertical kiln high calcium magnesium calcium zircon sand, 42 parts of 5mm~2mm oil vertical kiln high calcium magnesium calcium zircon sand, 26 parts of 2mm~0mm oil vertical kiln high calcium magnesium calcium zircon sand, 1 part of 5mm~2mm magnesium calcium titanium sand, 1 part of 2mm~0mm magnesium calcium titanium sand, 17 parts of oil vertical kiln high calcium magnesium calcium zircon sand fine powder ≤0.074mm, 3 parts of magnesium calcium titanium sand ultrafine powder ≤0.037mm, and 3 parts of composite binder;

[0085] The physical and chemical indicators of the high calcium magnesium calcium zirconium sand and magnesium calcium titanium sand in the oil shaft kiln of this embodiment are shown in Table 3.

[0086] The manufacturing method of the high calcium magnesium perovskite brick for stainless steel smelting has the same process steps as those of Example 1; the test results of the finished product of this example are shown in Table 6.

[0087] Comparative example 1.

[0088] A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting is made of the following raw materials in proportion by weight:

[0089] 10 parts of 8mm~5mm magnesium calcium sand, 40 parts of 5mm~2mm magnesium calcium sand, 25 parts of 2mm~0mm magnesium calcium sand, 3 parts of 5mm~2mm magnesium calcium titanium sand, 2 parts of 2mm~0mm magnesium calcium titanium sand, 5 parts of magnesium calcium sand fine powder ≤ 0.074mm, 5 parts of magnesium calcium titanium sand ultrafine powder ≤ 0.037mm, and 5 parts of composite binder;

[0090] The physical and chemical indicators of magnesium calcium titanium sand and magnesium calcium sand in this comparative example are shown in Table 4.

[0091] Table 4 Physical and chemical indicators of magnesium calcium titanium sand and magnesium calcium sand

[0092]

[0093] Note: % is mass percentage.

[0094] The preparation method of the high calcium magnesium perovskite zirconium brick for stainless steel smelting comprises the following process steps:

[0095] (1) Raw material crushing: The magnesium calcium sand and magnesium calcium titanium sand are crushed, screened and ground by a jaw crusher, a roll crusher and a Raymond mill to produce magnesium calcium sand granules with particle sizes of 8mm~5mm, 5mm~2mm and 2mm~0mm, magnesium calcium titanium sand granules with particle sizes of 5mm~2mm and 2mm~0mm, magnesium calcium titanium sand fine powder with a particle size of ≤ 0.074mm, and magnesium calcium titanium sand ultrafine powder with a particle size of ≤ 0.037mm;

[0096] (2) Premixing fine powders: The magnesium calcium sand fine powder and the magnesium calcium titanium sand ultrafine powder after the crushing in step 1 are mixed evenly according to the required weight ratio to obtain premixed fine powders;

[0097] (3) Preparation of composite binder: First, 35 parts of zirconium tetrachloride, 5 parts of ammonia and 5 parts of propanol are stirred evenly in a vacuum reactor, and then hydrolyzed, precipitated, filtered, dissolved and crystallized. Then, 55 parts of industrial dextrin are added and mixed in a closed container. The mixed solution is cooled and separated in a cooling tower to prepare the composite binder.

[0098] (4) Mixing: All raw materials are fed into a high-speed mixer according to the required weight for mixing. The order of adding materials is 8mm~5mm magnesium calcium sand first, then 5mm~2mm and 2mm~0mm magnesium calcium sand, 5mm~2mm and 2mm~0mm magnesium calcium titanium sand, then adding a composite binder and mixing, and finally adding the premixed fine powder in step 2;

[0099] (5) Molding: Weigh the specified weight of clay, evenly place it into the mold cavity of the brick press, and mold it under high pressure to obtain a molded brick;

[0100] (6) Stacking bricks: stacking the above-mentioned formed bricks on the tunnel kiln car;

[0101] (7) Firing: The kiln cart with the formed bricks is fired in a tunnel kiln at a high temperature of 1650°C to 1700°C;

[0102] (8) Sorting, processing and packaging: After the formed bricks are cooled out of the kiln, they are sorted, packaged and then put into the finished product warehouse.

[0103] The test results of the finished product of this comparative example are shown in Table 7.

[0104] Comparative example 2.

[0105] A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting is made of the following raw materials in proportion by weight:

[0106] 10 parts of 8mm~5mm oil vertical kiln high calcium magnesium calcium zircon sand, 40 parts of 5mm~2mm oil vertical kiln high calcium magnesium calcium zircon sand, 25 parts of 2mm~0mm oil vertical kiln high calcium magnesium calcium zircon sand, 3 parts of 5mm~2mm magnesium calcium sand, 2 parts of 2mm~0mm magnesium calcium sand, 5 parts of ≤ 0.074mm oil vertical kiln high calcium magnesium calcium zircon sand fine powder, 5 parts of ≤ 0.037mm magnesium calcium sand ultrafine powder, 5 parts of composite binder;

[0107] The physical and chemical indicators of the magnesium calcium sand and the oil shaft kiln high calcium magnesium calcium zirconium sand in this comparative example are shown in Table 5.

[0108] Table 5 Physical and chemical indicators of magnesium calcium sand and oil shaft kiln high calcium magnesium calcium zirconium sand

[0109]

[0110] Note: % is mass percentage.

[0111] The preparation method of the high calcium magnesium perovskite zirconium brick for stainless steel smelting comprises the following process steps:

[0112] (1) Raw material crushing: The oil shaft kiln high calcium magnesium calcium zircon sand and magnesium calcium sand are crushed, screened and ground by a jaw crusher, a roll crusher and a Raymond mill to produce oil shaft kiln high calcium magnesium calcium zircon sand granular materials with particle sizes of 8mm~5mm, 5mm~2mm and 2mm~0mm, magnesium calcium sand granular materials with particle sizes of 5mm~2mm and 2mm~0mm, oil shaft kiln high calcium magnesium calcium zircon sand fine powder with a particle size of ≤ 0.074mm, and magnesium calcium sand ultrafine powder with a particle size of ≤ 0.037mm;

[0113] (2) Premixing fine powder: the oil shaft kiln high calcium magnesium calcium zirconium sand fine powder and magnesium calcium sand ultrafine powder crushed in step 1 are mixed evenly according to the required weight ratio to obtain premixed fine powder;

[0114] (3) Preparation of composite binder: First, 35 parts of zirconium tetrachloride, 5 parts of ammonia and 5 parts of propanol are stirred evenly in a vacuum reactor, and then hydrolyzed, precipitated, filtered, dissolved and crystallized. Then, 55 parts of industrial dextrin are added and mixed in a closed container. The mixed solution is cooled and separated in a cooling tower to prepare the composite binder. The composite binder can make a large amount of secondary zirconium spinel appear between the magnesia sand particles in the brick, thereby improving the density and thus improving the high temperature resistance, corrosion resistance and slag resistance of the brick;

[0115] (4) Mixing: All raw materials are fed into a high-speed mixer according to the required weight for mixing. The order of adding materials is first 8mm~5mm oil shaft kiln high calcium magnesium calcium zircon sand, then 5mm~2mm and 2mm~0mm oil shaft kiln high calcium magnesium calcium zircon sand, 5mm~2mm and 2mm~0mm magnesium calcium sand, then add the composite binder and mix, and finally add the premixed fine powder in step 2;

[0116] (5) Molding: Weigh the specified weight of clay, evenly place it into the mold cavity of the brick press, and mold it under high pressure to obtain a molded brick;

[0117] (6) Stacking bricks: stacking the above-mentioned formed bricks on the tunnel kiln car;

[0118] (7) Firing: The kiln cart with the formed bricks is fired in a tunnel kiln at a high temperature of 1650°C to 1700°C;

[0119] (8) Sorting, processing and packaging: After the formed bricks are cooled out of the kiln, they are sorted, packaged and then put into the finished product warehouse.

[0120] The test results of the finished product of this comparative example are shown in Table 7.

[0121] Conventional magnesia-lime bricks are produced using magnesia sand, magnesia-lime sand and paraffin as raw materials and binders; the main raw materials of conventional magnesia-lime bricks are used to replace the high-calcium magnesia-calcium zircon sand and magnesia-calcium-titanium sand independently developed by the present invention for oil shaft kiln, and the conventional magnesia-lime brick binder paraffin is used to replace the composite binder mentioned in the present invention. After the test, the detection indicators are compared as shown in Table 6.

[0122] Table 6 Comparison of test indicators of the finished product of the embodiment of the present invention and conventional magnesia-lime bricks

[0123]

[0124] Note: The % of apparent porosity is volume percentage, and the remaining % is mass percentage.

[0125] Table 7 Comparison of test indicators of the finished product of Example 1 of the present invention and the finished product of the comparative example

[0126]

[0127] Note: The % of apparent porosity is volume percentage, and the remaining % is mass percentage.

[0128] From Table 6 and Table 7, we can see that:

[0129] (1) The high calcium magnesium calcium titanium zirconium brick for stainless steel smelting of the present invention is prepared by using high calcium magnesium calcium zirconium sand, magnesium calcium titanium sand and composite binder in an oil shaft kiln. The performance of the finished product is far superior to that of the existing magnesium calcium brick.

[0130] (2) By comparing the composite binder with the conventional paraffin binder, comparing the conventional magnesia-calcium sand to replace the high-calcium magnesia-calcium zircon sand of the oil shaft kiln, and comparing the conventional magnesia-calcium sand to replace the magnesia-calcium-titanium sand, it can be seen that the advantages of the innovative high-calcium magnesia-calcium zircon sand, magnesia-calcium-titanium sand and composite binder of the present invention over the currently used magnesia-calcium sand and paraffin binder.

[0131] In summary, the high calcium magnesium calcium titanium zirconium brick for stainless steel smelting of the present invention has high bulk density, low porosity, low impurities, high temperature resistance, corrosion resistance, slag resistance and high temperature wear resistance. With its innovation and excellent performance, it has become a replacement product of supporting refractory materials for stainless steel smelting. The clean steel effect is more obvious and has broad market advantages.

Claims

1. A high calcium magnesium calcium titanium zirconium brick for stainless steel smelting, characterized in that: The composition comprises the following raw materials in parts by weight: 5 to 13 parts of 8mm~5mm oil vertical kiln high calcium magnesium calcium zircon sand, 30 to 45 parts of 5mm~2mm oil vertical kiln high calcium magnesium calcium zircon sand, 12 to 25 parts of 2mm~0mm oil vertical kiln high calcium magnesium calcium zircon sand, 0 to 5 parts of 5mm~2mm magnesium calcium titanium sand, 0 to 5 parts of 2mm~0mm magnesium calcium titanium sand, 5 to 10 parts of ≤0.074mm oil vertical kiln high calcium magnesium calcium zircon sand fine powder, 5 to 10 parts of ≤0.037mm magnesium calcium titanium sand ultrafine powder, 3 to 5 parts of composite binder; The composite binder comprises the following raw materials in parts by weight: 30 to 40 parts of zirconium tetrachloride, 5 to 10 parts of ammonia, 5 to 10 parts of propanol, and 40 to 60 parts of industrial dextrin; the raw materials are mixed, cooled, separated, hydrolyzed and precipitated, filtered, dissolved and crystallized, and then prepared in a vacuum reactor; Magnesium calcium titanium sand: 93% of waste high-calcium dolomite and 7% of titanium concentrate are used as raw materials. After crushing, grinding and high-pressure ball pressing, they are put into an electric arc furnace for high-temperature calcination at above 2000℃. The finished product after calcination is kept warm for 8 hours, naturally cooled, and magnesium calcium titanium sand is selected.

2. The high calcium magnesium calcium titanium zirconium brick for stainless steel smelting according to claim 1, characterized in that: Oil vertical kiln high calcium magnesium calcium zirconium sand is made of 66% high-grade calcium hydroxide, 2% desiliconized zirconium and 32% light-burned magnesium powder in a mass ratio. After co-grinding, ball pressing, and calcination in a high-temperature oil vertical kiln, it is calcined at above 1680℃, naturally cooled, and crushed for selection.

3. The method for preparing high calcium magnesium perovskite bricks for stainless steel smelting according to any one of claims 1-2, characterized in that: The steps include: Step 1, raw material crushing: crush, screen and grind the high calcium magnesium calcium zirconium sand and magnesium calcium titanium sand of the oil shaft kiln into particles and fine powder of different particle sizes; Step 2, premixing fine powder: the oil shaft kiln high calcium magnesium calcium zirconium sand fine powder and magnesium calcium titanium sand ultrafine powder crushed in step 1 are mixed evenly according to the required mass fraction to obtain premixed fine powder; Step 3, mixing: the different granular raw materials in step 1 are fed into a high-speed mixer in the order of feeding for mixing for 5 minutes, and then the composite binder is added and mixed for 5 minutes, and then the fine powder premixed in step 2 is added and mixed for 8 minutes, and the material is discharged after mixing evenly to obtain a mud material; Step 4, molding: weigh the clay material of step 3 of a specified weight, evenly place it into the mold cavity of the brick press, and mold it under high pressure to obtain a molded brick; Step 5, stacking bricks: stacking the above-mentioned formed bricks on the tunnel kiln car; Step 6, firing: the kiln car with the formed bricks is fired at high temperature in a tunnel kiln; Step 7: Picking, processing and packaging: After the formed bricks are cooled out of the kiln, they are picked, packaged and then put into the finished product warehouse.

4. The method for preparing high calcium magnesium calcium titanium zirconium bricks for stainless steel smelting according to claim 3, characterized in that: Specifically, step 1 is to crush, screen and grind the oil shaft kiln high calcium magnesium calcium zircon sand and magnesium calcium titanium sand through a jaw crusher, a roll crusher and a Raymond mill to make oil shaft kiln high calcium magnesium calcium zircon sand granules with particle sizes of 8mm~5mm, 5mm~2mm, and 2mm~0mm, respectively, 5mm~2mm, 2mm~0mm magnesium calcium titanium sand granules, ≤0.074mm oil shaft kiln high calcium magnesium calcium zircon sand fine powder, ≤0.037mm magnesium calcium titanium sand ultrafine powder.

5. The method for preparing high calcium magnesium calcium titanium zirconium bricks for stainless steel smelting according to claim 3, characterized in that: In step 3, the order of adding materials is: first 8mm~5mm oil shaft kiln high calcium magnesium calcium zircon sand, then 5mm~2mm and 2mm~0mm oil shaft kiln high calcium magnesium calcium zircon sand, 5mm~2mm and 2mm~0mm magnesium calcium titanium sand, then add the composite binder to mix, and finally add the premixed fine powder in step 2.

6. The method for preparing high calcium magnesium calcium titanium zirconium bricks for stainless steel smelting according to claim 3, characterized in that: In step 6, the high temperature sintering temperature is 1650°C to 1700°C.

Citation Information

Patent Citations

  • Calcium zirconate and magnesia calcium zirconate brick prepared by calcium zirconate for cement kiln

    CN101759229A

  • Magnesia-calcium refractory material with high erosion resistance and preparation method thereof

    CN118290128A